How evidence based is English public health policy?. (17th November 2011) - Katikireddi, Srinivasa Vittal; Higgins, Martin; Bond, Lyndal; Bonell, Chris; Macintyre, Sally
Abstract : Srinivasa Vittal Katikireddi and colleagues ' analysis of the government's white paper Healthy Lives, Healthy People finds many of the interventions proposed lack evidence of effectiveness and some have even been shown not to work